2014
DOI: 10.1124/mol.114.092585
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human CYP2C9 Expression by Electrophilic Stress Involves Activator Protein 1 Activation and DNA Looping

Abstract: Cytochrome P450 (CYP)2C9 and CYP2C19 are important human enzymes that metabolize therapeutic drugs, environmental chemicals, and physiologically important endogenous compounds. Initial studies using primary human hepatocytes showed induction of both the CYP2C9 and CYP2C19 genes by tertbutylhydroquinone (tBHQ). As a pro-oxidant, tBHQ regulates the expression of cytoprotective genes by activation of redox-sensing transcription factors, such as the nuclear factor E2-related factor 2 (Nrf2) and members of the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Previously it was shown in human hepatocytes that upregulation of other phase I xenobiotic-metabolizing enzymes such as CYP2C19 and CYP2C9 is mediated by distinct activation of the AP-1 site in the promoters of these genes. It has been shown elsewhere, using specific kinase inhibitors, that extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) are essential for the tBHQ-induced expression, whereas Nrf2 has no effect [22]. We also observed induction of mRNA, protein expression, and activity of Cyp2b10, another CAR target gene (Table 1, Figs 3 and 4C).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previously it was shown in human hepatocytes that upregulation of other phase I xenobiotic-metabolizing enzymes such as CYP2C19 and CYP2C9 is mediated by distinct activation of the AP-1 site in the promoters of these genes. It has been shown elsewhere, using specific kinase inhibitors, that extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) are essential for the tBHQ-induced expression, whereas Nrf2 has no effect [22]. We also observed induction of mRNA, protein expression, and activity of Cyp2b10, another CAR target gene (Table 1, Figs 3 and 4C).…”
Section: Discussionsupporting
confidence: 68%
“…For Cyp1a1 , Cyp1a2 , and Cyp2b10 , we showed that this activation was also manifested in protein levels and activities. P450 induction by synthetic phenolic antioxidants has been observed previously [2022]. In some studies [20, 21], the researchers proposed that tBHQ induces Cyp1a1 as a ligand of AhR.…”
Section: Discussionmentioning
confidence: 81%
“…Immunoblotting experiments were performed in microsomes to detect CYP2C proteins before and after treatment with BF or dimethylsulfoxide (DMSO) controls. Microsomes were prepared from cultured human hepatocytes as previously described (Makia et al, 2014). Briefly, cells were suspended in ice-cold buffer (0.1 M potassium phosphate, pH 7.4, containing 0.25 M sucrose and 1 mM EDTA) and homogenized using a Potter-Elvehjem homogenizer.…”
Section: Methodsmentioning
confidence: 99%
“…Electrophoretic mobility shift assays (EMSAs) with the in vitro transcribed proteins were performed essentially as described (Makia et al, 2014) by incubating 2 ml of the in vitro translated PPARa and RXRa proteins with labeled double-stranded oligonucleotides containing the PPRE control and various DR1s. The sequences of the complementary oligonucleotides were as follows: PPRE control: forward, 59-CAGGGGACCAGGACA AAGGTCACGTTCGGGA-39, and reverse, 59-TCCCGAACGTGACCT TTGTCCTGGTCCCCTG-39; DR1-A: forward, 59-ACCCTATGTGAA CTTCGAACTTTGGTTGATG-39, and reverse, 59-CATCAACCAA AGTTCGAAGTTCACATAGGGT-39; DR1-B: forward, 59-AATTACTA CTTCCCTTTGCCCTGGATAAAGG-39, and reverse, 59-CCTTTATC CAGGGCAAAGGGAAGTAGTAATT-39; DR1BMut: forward, 59-AAT TACTACTTCGGTTTGCGGTGGATAAAGG-39, and reverse, 59-CCTT TATCCACCGCAAACCGAAGTAGTAATT-39; DR1-C: forward, TAAAA CCAAACACGTCTGACCCACATTTTAC-39, and reverse, 59-GTAAA ATGTGGGTCAGACGTGTTTGGTTTTA-39; and DR1-D: forward, 59-TAAAAAGAAAGGTCAAGGCAGGAGCCTCAGC-39, and reverse, 59-GCTGAGGCTCCTGCCTTGACCTTTCTTTTTA-39.…”
Section: Cyp2c8 Is a Novel Target Of Ppara In Human Livermentioning
confidence: 99%
“…PCR product was cloned into a pGL3‐Basic vector (Promega) upstream of the firefly luciferase. AP‐1 consensus sequences were mutagenized by QuickChange site‐directed mutagenesis as described . The complementary DNA of human c‐Jun was amplified by RT‐PCR from HuH7 cells and cloned into p3xFLAG‐CMV‐14 vector.…”
Section: Methodsmentioning
confidence: 99%